Predicting hemorrhage expansion in patients with hypertensive intracerebral hemorrhage: the HE-VSD-A2TP score - Zhu, Yingying; Lin, Luyang; Wang, Wei; Liu, Conghui; Dai, Peiling; Chen, Kai; Chen, Jian (Frontiers in Neurology, 2025)
BackgroundHematoma expansion (HE) in hypertensive intracerebral hemorrhage (HICH) is significantly associated with patient mortality. Early identification of HE would be planning for appropriate and aggressive management for improving outcome and containing HE. Existing HE prediction models show variable accuracy across settings. To address this limitation, we developed and validate a new predictive model to enhance the accuracy of HE in patients with HICH.MethodsWe conducted a retrospective cohort study using data from two centers. The primary outcome was the occurrence of HE within 24 h of symptom onset, defined as an increase in hematoma volume ≥33% or ≥12.5 mL on follow-up imaging. Logistic regression was used to identify independent predictors of HE, and the HE-VSD-A2TP score system was developed and validated.ResultsFive hundred and sixty seven patients in the derivation cohort and 378 patients in the validation cohort. The HE-VSD-A2TP score included age, uncontrolled blood pressure, hematoma volume, irregularity/lobulation shape, non-homogeneous density, presentation within 6 h from symptom onset to CT, and the use of anticoagulation/antiplatelet therapy. The HE-VSD-A2TP score demonstrated superior discrimination in predicting HE compared to existing models like PREDICT, 9-point, and BRAIN scores, with an AUC of 0.871(95%CI 0.839–0.904) in the derivation cohort and 0.858 (95%CI 0.819–0.897) in the validation cohort. The score also showed excellent calibration and outperformed other models in terms of sensitivity, specificity, likelihood ratios, negative predictive value, and positive predictive value. With regard to clinical usefulness, the decision curve analysis (DCA) of HE-VSD-A2TP showed higher net benefit than PREDICT, 9-point, and BRAIN scores in the both cohorts.ConclusionThe HE-VSD-A2TP score was validated to be an effective tool for identifying patients at risk of HE in patients with HICH. It was a valuable tool for guiding clinical management strategies and potentially improving patient outcomes.